The figure on the left has been transformed into the one on the right. Which transformation does this show?
A) (x', y') = (y, x)
B) (x', y') = (x, -y)
C) (x', y') = (-x, y)
D) (x', y') = (-y, x)

The figure on the left has been transformed into the one on the right Which transformation does this show A x y y x B x y x y C x y x y D x y y x class=

Respuesta :

(x', y') = (x, -y) is correct. The x-values do not change, but the y-values take on opposite signs. This is a reflection in the x-axis.

Answer:

Option B.

Step-by-step explanation:

The figure on the left has been transformed into the one on the right.

From the given diagram it is clear that the figure is reflected across x-axis.

If a figure reflected across x-axis, then the rule of reflection is

[tex](x,y)\rightarrow (x,-y)[/tex]

where, (x,y) is the ordered pair of image and (x,-y) is the ordered pair of preimage.

It means,

[tex](x',y')=(x,-y)[/tex]

The given transformation is represented by [tex](x',y')=(x,-y)[/tex].

Therefore, the correct option is B.

ACCESS MORE